The Influence of Customer and Technology Supply Chain Integration on Social Sustainable Performance with Moderating Role of Organizational Structure - Kittisak Jermsittiparsert; Thanaporn Sriyakul; Nuanluk Sangperm (International Journal of Supply Chain Management, 2019)
Supply chain management has taken attention of research scholars and emerging concept of greening supply chain activities in response to environmental concerns and social sustainable performance. The study aims to determine the relationship between supply chain integration and sustainable performance of automotive industry of Thailand. The study aims to determine the relationship between supplier integration, customer integration, and technological integration to determine sustainable social performance. The study also entails the moderating role of organizational structure between supplier, customer and technological integration and dependent variable sustainable social performance. The data was collected from automotive manufacturing industry of Thailand and analyzed by using SMART-PLS by measurement model and structural equation modeling techniques. The findings of the study demonstrated that all direct relations between independent and dependent variables were accepted, moderating role of organization structure was also observed, but the results found to be insignificant between customer integration and social sustainable performance at automotive manufacturing industry of Thailand.